Real‐Time Monitoring of New Delhi Metallo‐β‐Lactamase Activity in Living Bacterial Cells by 1H NMR Spectroscopy1. (22nd January 2014) - Ma, Junhe; McLeod, Sarah; MacCormack, Kathleen; Sriram, Shubha; Gao, Ning; Breeze, Alexander L.; Hu, Jun
Abstract Disconnections between in vitro responses and those observed in whole cells confound many attempts to design drugs in areas of serious medical need. A method based on 1D 1H NMR spectroscopy is reported that affords the ability to monitor the hydrolytic decomposition of the carbapenem antibiotic meropenem inside Escherichia coli cells expressing New Delhi metallo‐β‐lactamase subclass 1 (NDM‐1), an emerging antibiotic‐resistance threat. Cell‐based NMR studies demonstrated that two known NDM‐1 inhibitors, L‐captopril and ethylenediaminetetraacetic acid (EDTA), inhibit the hydrolysis of meropenem in vivo. NDM‐1 activity in cells was also shown to be inhibited by spermine, a porin inhibitor, although in an in vitro assay, the influence of spermine on the activity of isolated NDM‐1 protein is minimal. This new approach may have generic utility for monitoring reactions involving diffusible metabolites in other complex biological matrices and whole‐cell settings, including mammalian cells.